Strategi Eksperimen di Ruang Kelas: Bagaimana Mengubah Teori Menjadi Pengalaman Nyata - Indra Yuliasti; Muhammad Saleh; Besse Marjani Alwi (CV. ITTC INDONESIA, 2026)
Science learning in the 21st century demands a transformation from conventional approaches toward student-centered approaches to improve science literacy. This study aims to describe the concepts, theoretical foundations, implementation steps, as well as challenges and solutions in experimental learning strategies in schools and madrasas. The experimental learning strategy provides direct experience for students to prove concepts through scientific methods. This writing uses a qualitative descriptive method with literature study analysis and a review of best practices at MTs Darul Falah Enrekang on biotechnology material. The results show that experimental learning based on constructivism theory and experiential learning is able to significantly improve conceptual understanding and science process skills. Implementation at MTs Darul Falah proved an increase in students' average scores from 70 to 87. Despite facing challenges in the form of limited facilities and time, creative solutions such as the use of local materials and virtual laboratories proved effective. In conclusion, the experimental strategy is highly relevant for improving the quality of science learning as long as it is supported by teacher competence and creativity in resource management.